About Teleological Behaviorism - Rachlin, Howard (Behav Anal, 2013)
Misconceptions abound about teleological behaviorism (TB). Because very few people other than the author publicly call themselves teleological behaviorists, the fault must be mine. The present article is an attempt to clear up those misconceptions. First I will try to indicate what teleological behaviorism is not. Then, in the form of six fables (loosely connected stories, allegories, analogies, fairy tales, and arguments), I will try to give the reader an understanding of what teleological behaviorism actually is.